Corrections to “Evaluation of Machine Learning Approaches for Precision Farming in Smart Agriculture System: A Comprehensive Review” - Ghulam Mohyuddin; Muhammad Adnan Khan; Abdul Haseeb; Shahzadi Mahpara; Muhammad Waseem; Ahmed Mohammed Saleh (IEEE Access)
Presents corrections to the paper, Evaluation of Machine Learning Approaches for Precision Farming in Smart Agriculture System: A Comprehensive Review.